The Performance of Malaysian Manufacturing Sector Relationship Among Real Output, Employment, Labor Productivity and Real Wages in E&E Sub-Sector - Henry, Dority John (2011)
The Malaysian electronic and electrical sub-sector has been the most important component of the nation's manufacturing sector. As is widely known, the sector has played a vital role in the nation's export, employment as well as overall economic growth. Considering the importance of the subsector, it is imperative that we ensure sustainable growth of the sub-sector and that competitiveness is maintained or even improved. This study is particularly aimed at investigating the linkages between output, productivity, wage and labor. As is widely acknowledged, wages may increase as long as it is commensurate with a higher increase in productivity. However, changes in wages can actually affect employment. Unit root tests indicate that all of the above variables are 1(1). Johansen's procedure was conducted to see the long run relationships between the variables. The Johansen co integration test results revealed that a long-run equilibrium relationship exists among the variables. The relationships among the variables are tested by using Granger Causality Test and Ordinary Least Square teat. From the short run dynamic analysis, we found that except for real wages, labor productivity and employment are statistically significant in influencing output.